2015
DOI: 10.4049/jimmunol.1403045
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping of Human Macrophage Polarization through Modulation of Glucose Catabolic Pathways

Abstract: Macrophages integrate information from the tissue microenvironment and adjust their effector functions according to the prevalent extracellular stimuli. Therefore, macrophages can acquire a variety of activation (polarization) states, and this functional plasticity allows the adequate initiation, regulation, and resolution of inflammatory responses. Modulation of the glucose metabolism contributes to the macrophage adaptation to the surrounding cytokine milieu, as exemplified by the distinct glucose catabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 50 publications
3
70
0
Order By: Relevance
“…Our findings indicating (i) reduced ECAR levels as a result of BCAT1 inactivation in human macrophages and (ii) anti-inflammatory effects of ERG240, reversing the M1-like transcriptome in mouse peritoneal macrophages, argue in favour of the involvement of BCAA in M1/proinflammatory macrophage function. Although the metabolic response of murine macrophages and dendritic cells to LPS stimulation has been thoroughly explored1517, the bioenergetic profile of human macrophages is not well described and recent reports suggest that culturing conditions (M-CSF versus GM-CSF) play an important role in their metabolic reprogramming56. Here, we report that early LPS stimulation of human macrophages resulted in an increase of ECAR, which is indicative of increased glycolytic rate and is consistent with previous results obtained in murine bone marrow derived and peritoneal macrophages15.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicating (i) reduced ECAR levels as a result of BCAT1 inactivation in human macrophages and (ii) anti-inflammatory effects of ERG240, reversing the M1-like transcriptome in mouse peritoneal macrophages, argue in favour of the involvement of BCAA in M1/proinflammatory macrophage function. Although the metabolic response of murine macrophages and dendritic cells to LPS stimulation has been thoroughly explored1517, the bioenergetic profile of human macrophages is not well described and recent reports suggest that culturing conditions (M-CSF versus GM-CSF) play an important role in their metabolic reprogramming56. Here, we report that early LPS stimulation of human macrophages resulted in an increase of ECAR, which is indicative of increased glycolytic rate and is consistent with previous results obtained in murine bone marrow derived and peritoneal macrophages15.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased glycolysis and HIF-1α activity may also occur under aerobic conditions as demonstrated in cancer cells 4, 32 , and in the inflammatory differentiation of immune cells such as lymphocytes, myeloid cells and different type of fibroblasts 2, 1214, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that M‐CSF‐macrophages exhibit a unique M2‐like phenotype, different to the one of M2a‐c macrophages. A recent study has also reported that differences between human M‐CSF‐ and GM‐CSF‐macrophage properties can be extended to their metabolism . Similar to conventional M2 (elicited by IL‐4 or IL‐13) and M2‐like macrophages (i.e., M2b induced by IL‐1β and M2c induced by IL‐10), M‐CSF‐macrophages produce elevated levels of IL‐10 and low levels of IL‐12.…”
Section: Human Macrophage Differentiation Factorsmentioning
confidence: 98%